Challenges for implementing WFME standards for accreditation in health professions education in low and middle-income countries: a scoping review - Aisha Rafi; Muhammad Idrees Anwar (Journal of the Pakistan Medical Association, 2020)
Abstract The accreditation standards developed by WFME are acknowledged as regulatory mechanism for quality assurance of medical education programs. The scoping review aims to collect all the published and unpublished evidence based on the inclusion criteria, to identify the barriers affecting the implementation of quality curriculum defined by WFME. It summarizes and presents the evidence-based challenges faced by middle and low income countries for accreditation process. The literature was searched using search terms, `challenges of WFME accreditation’, `barriers to accreditation’, `challenges to accreditation in health care system’, `hindrances to WFME accreditation standards’, `barriers to WFME standards’, in PubMed, ERIC, PsycINFO databases and Google scholar (for grey literature) to find the evidence published within last 10 years. This search strategy retrieved 922 publications and only 19 articles fulfill the inclusion criteria. A All those studies, which address the barriers or challenges to implementation of accreditation standards in medical education, were included. The inhibitors to implementation of curriculum in course other than medical education were excluded from the study. The included studies address the barriers to nine areas of WFME standards. The data was charted and QualSyst appraisal tool was used to appraise the quality of studies included in review. The eligibility of selected articles was carried out by using the validated QualSyst checklist to assess the quality of included studies. The scoping review will inform and lay the foundation for more empirical studies on quality improvement in health professions education particularly in low and middle-income countries. Keywords: Challenges of accreditation,